Estilos de Afrontamiento en personas con Lesiones de Piel por Quemaduras de II y III Grado - Maldonado Vega, María del Pilar; Rodríguez Rodríguez, Elssy Yurany (Universidad Antonio Nariño, 2024)
The present investigation aims to describe the coping styles in 40 people with skin lesions from burns II and III, the theoretical foundations for this research were based on the cognitivebehavioral approach from the theoretical perspective of Lazarus and Folkman; In this way, the methodology used was quantitative, cross-sectional and descriptive. Likewise, data collection is done through a sociodemographic survey and the Brief Cope questionnaire. Finally, a quantitative analysis of the results is carried out taking into account the coping strategies; In this way it is concluded that the style of coping most used by the participants was focused on the problem.